Implementation and Evaluation of Online Life Skills Training Modules for Therapy Assistant Students at a Canadian College - Raudebaugh, Candi; Finlayson, Marcia; Norman, Kathleen; Stewart, Sally (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2024)
Like all college students, therapy assistant students may face challenges in daily living skills, such as money management, time management, and healthy meal preparation, which may negatively impact their academic and practicum success. Therapy assistant students face the added challenge of working on life skills with clients, and, as a result, students’ own life skills may affect their success in clinical encounters. Few life skills training programs exist for post-secondary students, and we were unable to find any for therapy assistant students.This study is the third phase of a larger research project that developed, implemented, and evaluated life skills training modules for therapy assistant students. Life skills training modules were offered online to therapy assistant students at a Canadian college to explore whether life skills training increased students’ knowledge, self-rated competence in occupations, and self-efficacy related to personal life skills. Findings revealed that students’ knowledge quiz scores significantly improved, and students rated the modules positively in respect to learning and satisfaction. No significant change was detected in students’ Occupational Self Assessment (OSA) scores. Online life skills training modules may be beneficial for therapy assistant students to increase their knowledge about life skills and meet identified needs.